Allosteric modulation of the chemokine receptor-chemokine CXCR4-CXCL12 complex by tyrosine sulfation - Sonawani, Archana; Kharche, Shalmali; Dasgupta, Debjani; Sengupta, Durba (International Journal of Biological Macromolecules, 2022)
The chemokine receptor CXCR4 and its cognate ligand CXCL12 mediate pathways that lead to cell migration and chemotaxis. Although the structural details of related receptor-ligand complexes have been resolved, the roles of the N-terminal domain of the receptor and post-translational sulfation that are determinants of ligand selectivity and affinity remain unclear. Here, we analyze the structural dynamics induced by receptor sulfation by combining molecular dynamics, docking and network analysis. The sulfotyrosine residues, 7YsN-term, 12Ys(N-term) and 21Ys(N-term) allow the N-terminal domain of the apo-sulfated receptor to adopt an ``open `` conformation that appears to facilitate ligand binding. The overall topology of the CXCR4-CXCL12 complex is independent of the sulfation state, but an extensive network of protein-protein interactions characterizes the sulfated receptor, in line with its increased ligand affinity. The altered interactions of sulfotyrosine residues, such as 21Ys(N-term)- 47R(CXCL12) replacing the 21Y(N-term)-13F(CXCL12) interaction, propagate via allosteric pathways towards the receptor lumen. In particular, our results suggest that the experimentally-reported receptor-ligand interactions 262D(6.58)- 8R(CXCL12) and 277E(7.28)-12R(CXCL12) could be dependent on the sulfation state of the receptor and need to be carefully analyzed. Our work is an important step in understanding chemokine-receptor interactions and how post-translational modifications could modulate receptor-ligand complexes.
Keywords: Allosteric communication pathway; Atomistic molecular dynamics simulations; G protein-coupled receptor; Ligand binding; Post-translational modification; Protein-protein interface

Graphical Biology Insights into the dynamic interactions at chemokine-receptor interfaces and mechanistic models of chemokine binding - Sonawani, Archana; Kharche, Shalmali; Dasgupta, Debjani; Sengupta, Durba (Journal of Structural Biology, 2022)
Chemokine receptors are the central signaling hubs of several processes such as cell migration, chemotaxis and cell positioning. In this graphical review, we provide an overview of the structural and mechanistic principles governing chemokine recognition that are currently emerging. Structural models of chemokine-receptor cocomplexes with endogenous chemokines, viral chemokines and therapeutics have been resolved that highlight multiple interaction sites, termed as CRS1, CRS1.5 etc. The first site of interaction has been shown to be the Nterminal domain of the receptors (CRS1 site). A large structural flexibility of the N-terminal domain has been reported that was supported by both experimental and simulation studies. Upon chemokine binding, the Nterminal domain appears to show constricted dynamics and opens up to interact with the chemokine via a large interface. The subsequent sites such as CRS1.5 and CRS2 sites have been structurally well resolved although differences arise such as the localization of the N-terminus of the ligand to a major or minor pocket of the orthosteric binding site. Several computational studies have highlighted the dynamic protein-protein interface at the CRS1 site that seemingly appears to resolve the differences in NMR and mutagenesis studies. Interestingly, the differential dynamics at the CRS1 site suggests a mixed model of binding with complex signatures of both conformational selection and induced fit models. Integrative experimental and computational approaches could help unravel the structural basis of promiscuity and specificity in chemokine-receptor binding and open up new avenues of therapeutic design.
Keywords: Chemokine receptors; GPCRs; Intrinsically disordered protein domains; protein-protein interactions